Evaluasi Kinerja Guru di SDN Giricahyo Ditinjau dari Standar Standar Kinerja Guru: Studi Kualitatif - Saputra, Dewan; Satrio Nugroho, Mohammad Awal (Economic Reviews Journal, 2025)
This study aims to improve teacher performance at Giricahyo Elementary School based on Teacher Performance Standards, which include pedagogical, professional, social, and personality competencies, and to identify influencing factors and improvement strategies. This study uses a qualitative approach with a case study method, through in-depth interviews, observation, and documentation involving teachers and the principal as key informants. The results show that teacher performance at Giricahyo Elementary School generally meets competency standards, especially in personality and social aspects. Teachers demonstrate responsibility, discipline, and good relationships with students. However, there are still obstacles in the pedagogical and professional aspects due to limited infrastructure and high workloads. The main supporting factors include intrinsic motivation, principal supervision, and a collaborative work environment. This study recommends increasing academic supervision in a coaching manner, strengthening the Teacher Learning Community (KoMbel), and implementing a performance-based system. The results of this study are expected to provide input for schools and local governments in improving the quality of education through effective teacher performance.